The Effect of Gender Empowerment and Women's Income on Poverty in Indonesia: Economic Growth as a Moderating Variable - Mahzanallah, M.; Amri, Khairul; Fitri , Cut Dian (Manunggal Halim Jaya, 2025)
The results show that gender empowerment positively influences poverty, although it is not statistically significant. Meanwhile, women's income has a negative and significant effect on the poverty rate, which means that the higher the contribution of women's income in the household, the lower the poverty rate. In addition, economic growth also has an adverse effect on poverty, which indicates that an increase in a region's economy contributes to reducing poverty. However, in the moderation analysis, economic growth does not significantly strengthen or weaken the relationship between gender empowerment and women's income and poverty. These findings provide insights for the government in designing more effective poverty alleviation policies by considering gender empowerment and increasing women's income.